Social Anxiety and Social Phobia in Youth - Kearney, Christopher A. (Springer, 2005)
A great benefit of being a clinical child psychologist is the opportunity to conduct and review research on fascinating areas of human, youthful behavior.Andperhaps no behavior is as central tohumanexistence as social behavior, and the lack thereof. In writing this book, therefore, I have been doubly blessed with the chance to examine seminal works on behaviors that are so critical to the development and quality of life of children. This book covers the major historical aspects, characteristics, assessment strategies, and psychological treatment techniques for youths with social anxiety and social phobia. Chapter 1 provides an introduction to the related constructs and history of social phobia. Chapters 2 and 3 provide a summary of the characteristics and etiological variables that pertain most to youths with social anxiety and social phobia. Chapters 4 and 5 provide an overview of research- and clinically-based assessment strategies and recommendations for this population. Chapters 6–9 provide a description of treatment techniques that are most relevant and empirically supported for youths with social anxiety and social phobia. Chapter 10 covers issues regarding general and relapse prevention as well as difficult cases and future directions. This book is intended for a wide array of audiences, including clinical and counseling psychologists, school and educational psychologists, social workers, psychiatrists, pediatricians, guidance counselors, principals, teachers, and other relevant professionals. In general, though, the book is meant for those who simply wish to gain a better knowledge of youths with social anxiety and social phobia. The literature in this area is growing fast, and keeping up with the technologies that have been developed to measure and address this important population is crucial.
Characteristics, Assessment, and Psychological Treatment